THERMAL PRESSURE IN THE LASER-HEATED DIAMOND-ANVIL CELL: AN X-RAY DIFFRACTION STUDY - Andrault D.; Richet P.; Piquet G.; Gillet P.; Itié J.P.; Häusermann D.; Hanfland M. (My University, 1998)
Using X-ray diffraction with synchrotron radiation, we have studied the pressure changes induced by laser heating on samples compressed in a diamond-anvil cell. The method has been to compare experimentally observed phase transitions of Mg2SiO4 and SiO2 polymorphs with well-constrained phase diagrams and equations of state reported in the literature. Our results clearly demonstrate an increase of pressure in the laser hot spot with respect to the nominal pressure measured from the ruby fluorescence at room temperature. At 2200 ± 100 K, for instance, wadsleyite has been synthesized from forsterite at a nominal pressure of 11 Gpa, which is 4 GPa lower than the reported transition pressure. In addition, the measured high-pressure, high-temperature molar volumes of forsterite and wadsleyite appear much smaller than those calculated from available thermoelastic data. Taking into account this pressure increase, we reconcile conflicting experimental determinations of the coesite-stishovite transition made with multi-anvil press and diamond-anvil cell. The pressure change induced by laser heating is a function of the product of the thermoelastic coefficients α (thermal expansion) and K(T) (bulk modulus) of the sample. We thus stress the need for an internal pressure standard, such as Pt, Au or MgO for determining equations of state and phase equilibria under the P-T conditions prevailing in the Earth's mantle and core.